Study of Acute Kidney Injury in Patients Hospitalized with COVID-19: A Single Center Study in Bangladesh - Rasul, Md Maqsudur; Rahman, AKM Mijanur; Rahman, Azizur; Hussain, Tahmeed; Nath, Sanjoy Kanto; Joha, Miskat; Haque, Dewan Mohaimenul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: The incidence of acute kidney injury (AKI) associated with hospitalized corona virus disease -19(Covid- 19) patients and associated outcomes are not well determined. This study describes the presentation, risk factors and outcomes of AKI in patients hospitalized with Covid-19. Material & Methods: In this cross sectional study, we reviewed the health records for all conveniently selected patients hospitalized with Covid-19 irrespective of co morbidity from 1st May to 31st July, 2020, at combined military hospital Dhaka, Bangladesh. Patients younger than 18 years, end stage kidney disease or with a kidney transplant recipient were excluded from the study. AKI was deûned according to kidney disease improving global outcome (KDIGO) criteria. Results: A total of 470 Covid-19 patients were recruited in this current study, out of them 67.02% were male and 32.98% of were female; with male to female ratio was 2:1. The mean age of the study population was 54.71(±14.31) years. AKI developed among 106 (22.55%) patients of whom 50 patients had CKD. The peak stages of AKI were stage 3 in 58(12.34%), followed by stage 1 in 37(7.87%), and stage 2 in 11(2.34%) patients. Renal replacement therapy was required (RRT) for 37(7.87%) patients. Risk factors included older age, hypertension, diabetes mellitus, cardiovascular disease, and chronic kidney disease and those who presented with prolong fever and breathlessness.AKI was commonly seen in patients with severe disease. Considerable number of patient had proteinuria 222(47.23%) and haematuria in 63 (13.40%) and were significantly associated with AKI. Elevated level of ferritin, D-dimer and procalcitonin were observed among 249(52.98%), 179(38.08%) and 138(35, 88%) patients respectively which were substantially correlated with AKI. COVID-19 patients complicated to acute kidney injury were strongly associated with higher mortality19 of 23 (82.60%). Conclusion: Renal involvement in COVID-19 (Corona virus-nephropathy) has a complex etiology. It is closely associated with severity of disease and indicating poor prognosis. Further study will be needed for better understanding the causes of AKI and patient outcomes. J Bangladesh Coll Phys Surg 2022; 40: 79-86